Water uptake is independent of the inferred composition of secondary aerosols derived from multiple biogenic VOCs - M. R. Alfarra; N. Good; K. P. Wyche; J. F. Hamilton; P. S. Monks; A. C. Lewis; G. McFiggans (Atmospheric Chemistry and Physics, 2013)
We demonstrate that the water uptake properties derived from sub- and super-saturated measurements of chamber-generated biogenic secondary organic aerosol (SOA) particles are independent of their degree of oxidation, determined using both online and offline methods. SOA particles are formed from the photooxidation of five structurally different biogenic VOCs, representing a broad range of emitted species and their corresponding range of chemical reactivity: α-pinene, β-caryophyllene, limonene, myrcene and linalool. The fractional contribution of mass fragment 44 to the total organic signal (f44) is used to characterise the extent of oxidation of the formed SOA as measured online by an aerosol mass spectrometer. Results illustrate that the values of f44 are dependent on the precursor, the extent of photochemical ageing as well as on the initial experimental conditions. SOA generated from a single biogenic precursor should therefore not be used as a general proxy for biogenic SOA. Similarly, the generated SOA particles exhibit a range of hygroscopic properties, depending on the precursor, its initial mixing ratio and photochemical ageing. The activation behaviour of the formed SOA particles show no temporal trends with photochemical ageing. The average κ values derived from the HTDMA and CCNc are generally found to cover the same range for each precursor under two different initial mixing ratio conditions. A positive correlation is observed between the hygroscopicity of particles of a single size and f44 for α-pinene, β-caryophyllene, linalool and myrcene, but not for limonene SOA. The investigation of the generality of this relationship reveals that α-pinene, limonene, linalool and myrcene are all able to generate particles with similar hygroscopicity (κHTDMA ~0.1) despite f44 exhibiting a relatively wide range of values (~4 to 11%). Similarly, κCCN is found to be independent of f44. The same findings are also true when sub- and super-saturated water uptake properties of SOA are compared to the averaged carbon oxidation state (OSC) determined using an offline method. These findings do not necessarily suggest that water uptake and chemical composition are not related. Instead, they suggest that either f44 and OSC do not represent the main dominant composition-related factors controlling water uptake of SOA particles, or they may emphasise the possible impact of semi-volatile compounds on limiting the ability of current state-of-the-art techniques to determine the chemical composition and water uptake properties of aerosol particles.